2015
DOI: 10.1186/s13047-015-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Primary care referral to multidisciplinary high risk foot services – too few, too late

Abstract: BackgroundTo determine if patients with no contact with a multi-disciplinary team High Risk Foot Service (MDT-HRFS) had an increased rate of hospital admission for diabetes foot infection compared to patients with contact. Secondary aims were to report on clinical outcomes.MethodsA retrospective study was conducted at a major tertiary referral hospital in metropolitan Sydney over 12 months. An ICD-10 search of the electronic medical record system and paper medical charts identified patients with diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Podiatrists are sole leaders in one article [48]. In 8 articles, they had a secondary role (support to the MDT but without a leading role) [45,46,49,51,56,58,60,61] and in 2 articles, they had a tertiary role (external consultation when needed) [38,42]. Podiatrists' role was similar to other team members in two articles [50,57] .…”
Section: Description Of Included Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Podiatrists are sole leaders in one article [48]. In 8 articles, they had a secondary role (support to the MDT but without a leading role) [45,46,49,51,56,58,60,61] and in 2 articles, they had a tertiary role (external consultation when needed) [38,42]. Podiatrists' role was similar to other team members in two articles [50,57] .…”
Section: Description Of Included Articlesmentioning
confidence: 99%
“…According to our predefined secondary outcomes (Table 1), data was available for mortality/survival [36,41,43,54,58], recurrence [43,54,57], other complications [54,61,64], and healthcare data [49,54,56,57,59,61,63,64]. Meta-analyses were performed for some studies, but heterogeneity was over 75%.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Whilst the current literature on multidisciplinary teams and their role in the management of DFI suggests that MDTs improve the health outcomes of patients (7)(8)(9)(10)12), the impact of a MDT on LOS and the degree of surgical intervention is not well established. This audit aimed to determine the effect of MDT involvement had on LOS and surgical outcomes of DFI patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found 27.1% of patients with previous antimicrobial use. These data were collected in order to try to correlate the use of antimicrobials with bacterial resistance, but this also serves to demonstrate the unsuccessful strategy of outpatient treatment in cases of DFI that evolve to moderate or severe due to the conditions of vascularization of the limbs [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%